ANALISIS KELAYAKAN FINANSIAL USAHA TANAMAN HIAS LISMA JAYA NURSERY DI KAMPUNG MUARA PRAFI DISTRIK MASNI KABUPATEN MANOKWARI - Husnul Fahria; Ishak Suwardi; Ardha Puspita Sari (Sosio Agri Papua, 2020)
Manokwari Regency is one of the districts in West Papua Province that is quite developed and has rapid changes and a strong enough attraction for some people to take advantage of opportunities to develop ornamental plant businesses. Lisma Jaya Nursery is one of the businesses in the field of ornamental plant agribusiness, which is located in Muara Prafi Village, Masni District, Manokwari District with a fairly large scale of business. Since the establishment of the business, Lisma Jaya Nursery has never conducted a financial analysis, therefore a financial analysis is needed to see whether this business is feasible or not to run and see how much this business can generate profits. The analytical method in this study is a quantitative analysis to assess financial viability by assessing investment criteria which include Net Present Value (NPV), Net Benefit Cost Ratio (Net B / C), Internal Rate of Return (IRR), and Payback Period (PP) . The results of the analysis of the financial aspects of the Lisma Jaya Nursery business were also declared feasible because the assessment carried out using investment criteria showed results that were in accordance with the eligibility assessment requirements. Based on investment eligibility criteria, the NPV value generated by ornamental plant businesses at a deposit rate of 5.75 percent is 732,653,424 which is greater than zero. The B / C ratio value resulting from the calculation is greater than one which is 4.3. The IRR value obtained is 59.1 percent which is greater than the deposit interest rate of 5.75 percent and a PP value of 2.5 which indicates that the return on investment is after 2 years and 5 months from the business carried out and not more than the age business used is 5 years.